2018
DOI: 10.1042/bsr20180411
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal polypeptide derived from vMIP-II exerts its anti-tumor activity in human breast cancer by regulating lncRNA SPRY4-IT1

Abstract: Accumulating evidence demonstrates that long non-coding RNA (lncRNA) sprouty4-intron transcript 1 (lncRNA SPRY4-IT1) plays a vital role in the development of breast cancer. However, the underlying mechanism has not been eventually illuminated. We aimed to explore the biological activity of lncRNA SPRY4-IT1 in breast cancer cells and whether N-terminal polypeptide derived from viral macrophage inflammatory protein II (NT21MP) could exert its anti-tumor effect by regulating lncRNA SPRY4-IT1 and its target gene S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Recently, SKA2 was also identified to exert a function in tumorigenesis. Aberrant expression patterns of SKA2 have been reported in lung cancer (27)(28)(29), breast cancer (30)(31)(32), osteosarcoma (33,34) and kidney cancer (35). Nevertheless, the potential roles of SKA2 in GC are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SKA2 was also identified to exert a function in tumorigenesis. Aberrant expression patterns of SKA2 have been reported in lung cancer (27)(28)(29), breast cancer (30)(31)(32), osteosarcoma (33,34) and kidney cancer (35). Nevertheless, the potential roles of SKA2 in GC are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…SPRY4‐IT1 acted as a factor which promoted progression of hepatocellular carcinoma by interacting with HNRNPL and influencing TNF signaling pathway 25 ; in non‐small‐cell lung cancer, SPRY4‐IT1 was an effective biomarker regulated by EZH2 40 ; high expression of SPRY4‐IT1 in colorectal cancer predicted poor prognosis 41,42 ; PI3K/Akt signaling pathway was activated by SPRY4‐IT1 in testicular germ cell tumor, meanwhile, cell growth, migration, and invasion were significantly enhanced 43 . Additionally, some studies confirmed SPRY4‐IT1 acted as an oncogene in breast cancer which related to poor prognosis, 44–46 however, the underlying mechanism of SPRY4‐IT1 promoting breast cancer was still fuzzy.…”
Section: Discussionmentioning
confidence: 92%
“…high expression of SPRY4-IT1 in colorectal cancer predicted poor prognosis 41,42 ; PI3K/Akt signaling pathway was activated by SPRY4-IT1 in testicular germ cell tumor, meanwhile, cell growth, migration, and invasion were significantly enhanced. 43 Additionally, some studies confirmed SPRY4-IT1 acted as an oncogene in breast cancer which related to poor prognosis, [44][45][46] however, the underlying mechanism of SPRY4-IT1 promoting breast cancer was still fuzzy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that lncRNA SPRY4‐IT1 is associated with the progress of breast cancer. LncRNA SPRY4‐IT1 is highly expressed in breast cancer cells, and N‐terminal polypeptide derived from viral macrophage inflammatory protein Ⅱ (NT21MP) inhibits the biological functions of breast cancer cells through lncRNA SPRY4‐IT1 . Another study has reported that proliferation is significantly suppressed when SPRY4‐IT1 is knocked down in breast cancer cells by targeting ZNF703 .…”
Section: Discussionmentioning
confidence: 99%